2018
DOI: 10.21276/ijcmr.2018.5.4.27
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum β Lactamase Producing Lactose Fermenters Causing Neonatal Septicaemia in a Tertiary Care Center in Uttar Pradesh

Abstract: Introduction: Extended-spectrum Beta-lactamase (ESBL) producing enterobacteriaceae are of escalating concern in today's antibiotic era especially in neonatal sepsis. This study was conducted to determine the prevalence of ESBL producing E.coli and Klebsiella species in neonatal sepsis. Material and Methods: This cross sectional study included 382 samples with signs and symptoms of neonatal sepsis. Blood cultures were done and the isolates were identified using standard biochemical tests and antibiotic suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
3
0
0
Order By: Relevance
“…Using phenotypic the prevalence of ESBL producing Gram-negative bacilli isolates was 51.6% (166/322). Our results were comparable with those of Mishra et al [41]. Another study showed that 48.3% of their cefotaxime resistant Gram-negative bacilli were ESBL producers [42].…”
Section: Phenotypic Detectionsupporting
confidence: 91%
“…Using phenotypic the prevalence of ESBL producing Gram-negative bacilli isolates was 51.6% (166/322). Our results were comparable with those of Mishra et al [41]. Another study showed that 48.3% of their cefotaxime resistant Gram-negative bacilli were ESBL producers [42].…”
Section: Phenotypic Detectionsupporting
confidence: 91%
“…of ESBL production was seen among Klebsiella pneumoniae (54.17%) and E. coli (44.44%). This was similar to results of Khanna et al, 2016, Prem Mishra et al, 2018and Gandhi et al, 2013 In the present study, 89 -100% resistance against 3 rd generation cephalosporins was observed among ESBL producing strains of Klebsiella pneumoniae and E. coli. Similar results reported by Islam et al, 2014 which reported all ESBL positive strains of E. coli were resistant to Cefotaxime, Ceftriaxone and Ceftazidime as compared to non ESBL isolates (30 -71%).…”
Section: Resultssupporting
confidence: 93%
“…Bacteriological profile of Neonatal Septicemia Distribution of culture positive cases among EONS & LONS cases ESBL production in Gram negative bacterial isolates Klebsiella pneumoniae and E. coli. This was in line with results of PremMishra et al, 2018. …”
supporting
confidence: 93%